2015
DOI: 10.1002/mar.20786
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Ownership of Brands and Counterfeits: Conceptualization and Temporal Transformation from a Consumer Perspective

Abstract: The aim of this paper is to shed light on consumers’ concurrent ownership of original and counterfeit versions of a brand, a phenomenon that is lively in the global market place but has thus far failed to attract adequate research attention. Using findings from eight focus group discussions, this paper investigates the relationships consumers have with brands and counterfeits when they own both at the same time, based on different object‐, self‐, and other‐centered engagements. Subsequently, three distinct con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 61 publications
(142 reference statements)
1
44
0
4
Order By: Relevance
“…For this group of customers, the choice of counterfeits is clearly not income-related. While they are interested in original brands, they prefer a counterfeit version for certain reasons--such as fun, pleasure, and excitement (Yoo & Lee, 2009)--and circumstances--for example, to protect the original from wearing out during travel (Gentry, Putrevu, & Shultz, 2006;Gistri, Romani, Pace, Gabrielli, & Grappi, 2009;Stöttinger & Penz, 2015). The Internet as a distribution channel allows these consumers to gain even further access to fakes because it broadens the number of products to choose from.…”
Section: Why Changes In Consumer Purchase Behavior Regarding Counterfmentioning
confidence: 96%
“…For this group of customers, the choice of counterfeits is clearly not income-related. While they are interested in original brands, they prefer a counterfeit version for certain reasons--such as fun, pleasure, and excitement (Yoo & Lee, 2009)--and circumstances--for example, to protect the original from wearing out during travel (Gentry, Putrevu, & Shultz, 2006;Gistri, Romani, Pace, Gabrielli, & Grappi, 2009;Stöttinger & Penz, 2015). The Internet as a distribution channel allows these consumers to gain even further access to fakes because it broadens the number of products to choose from.…”
Section: Why Changes In Consumer Purchase Behavior Regarding Counterfmentioning
confidence: 96%
“…Besides functional and social values, products can also satisfy individual needs such as materialism and enhancing self‐concept (Nia & Zaichkowsky, ). Prior research has found that individual characteristics such as materialism and perception of self‐image have a strong impact on counterfeit purchases (Eisend & Schuchert‐Güler, ; Kozar & Marcketti, ; Penz & Stöttinger, ; Stöttinger & Penz, ; Yoo & Lee, ). In this study, we use self‐clarity and materialism to capture the impact of individual values on the purchase intention of shanzhai products and counterfeit products.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…Historically music piracy research has its roots to anti-counterfeiting research and has been addressed by research highlighting the billions lost globally from the industry (Albers-Miller, 1999;Herstein, Drori, Berger, & Barnes, 2015;Stottinger & Penz, 2015). Most piracy studies that were conducted before the turn of the millennium were based on traditional software piracy of software duplication.…”
Section: Music Piracymentioning
confidence: 99%